(untitled) (Docentes 2.0 Journal, 2024)
Educational ethics and the problem of plagiarism once again gain notoriety and become topics of obligatory discussion. The essay aimed to analyze ethics and academic plagiarism and sought to answer the question: Have legal punishments been applied to those accused of academic plagiarism in Mexico? An issue that has been revived in recent months as a result of the problem. Esquivel Mossa, minister of the Supreme Court of Justice of the Nation (SCJN), is involved, initially accused of plagiarism in her bachelor’s thesis and later in the one corresponding to the doctorate, questioning from the end of December 2022. The article used the deductive method, the hermeneutic paradigm, with a qualitative interpretive approach and a narrative design. In Mexico, most public and private universities do not have express powers to punish and sanction academic plagiarism. In this regard, no isolated thesis or jurisprudence allusive to the issue of this dishonesty was found in the SCJN. In contrast, three cases were found in Colombia, where the Supreme Court of Justice promptly ruled and punished the plagiarism detected in a degree thesis.